Economic imperatives for forming the competitiveness of developer enterprises in a dynamic environment - Ryzhakova, G.; Krupnyk, D.; Davydenko, O.; Lavrynenko, O.; Herasymenko, O.; Yarush, D. (Ways to Improve Construction Efficiency, 2022)
The paper substantiates a system of economic imperatives and managerial mechanisms that ensure sustainable competitiveness of developer enterprises in a dynamic environment. It shows that performance and productivity are shaped not only by on-site parameters, but primarily by the quality of the “innovation ↔ economics” linkage: the integration of BIM 4D/5D, digital twins, IoT, and process mining with financial discipline (cost of capital, project finance, cadence of pre-sales, scenario and CVaR analysis). The concept of economic balance of the corporate portfolio is formulated as the capability to maintain target metrics of liquidity, profitability, and risk resilience under varying demand, input costs, and regulatory constraints; key levers include stage, product, and geographic diversification, phased roll-outs, launch/pause options, risk-sharing contract models, and long-term supply agreements. Roadmaps are justified for different management horizons: operational (EVM + Lean KPI to stabilize pace and budget), tactical (DES and process mining to remove approval and logistics bottlenecks), and strategic (a portfolio-level digital twin with NPV/IRR scenarios, Monte Carlo, CVaR, and ESG constraints). A system of cost–performance indicators is proposed to translate the “cost of time,” schedule/quality risks, and carbon-energy intensity into comparable decision metrics; it is demonstrated that ESG integration directly affects access to capital and product liquidity. The practical value lies in standardizing dashboards and trigger policies for portfolio management that enable early deviation detection, shorten time to positive cash flow, and reduce sensitivity to market shocks, financing costs, and regulation. The results are applicable to corporate planning and controlling systems of development companies.